Prevalence and Risk Factors of Urinary Tract Infections in Pregnant Women: A Cross-Sectional Study - Hashmat Ullah Khan, Uzma Afridi, Asma Hameed, Shahjehan, Sakina Naeem, Aliya Zaman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Urinary-tract infection (UTI) is a frequent antenatal complication that can provoke pyelonephritis, pre-term labour and low birth weight. Contemporary Pakistani prevalence data are limited. Objectives: To measure UTI prevalence in pregnant women at two tertiary centres and identify significant risk factors. Methods: A cross-sectional study was conducted at Lady Reading Hospital MTI Peshawar and Mayo Hospital Lahore between January 2022 and January 2023. Seventy pregnant women aged 18-45 years, recruited consecutively in any trimester, completed a structured interview capturing socio-demographic variables, anaemia and hygiene practices, then provided mid-stream urine. Cultures ≥10⁵ CFU mL⁻¹ defined infection; antibiotic susceptibility was determined by Kirby–Bauer. Associations were assessed with logistic regression. Results: Twenty-one women were culture-positive, yielding a prevalence of 30.0 %. Escherichia coli predominated (61.9 %), followed by Klebsiella pneumoniae (19.0 %) and Proteus mirabilis (9.5 %). Independent predictors were primigravidity (adjusted odds ratio [AOR] 3.1; 95 % CI 1.1-9.0), low socio-economic status (AOR 4.4; 1.4-13.8), haemoglobin < 10 g dL⁻¹ (AOR 3.6; 1.2-10.7), poor perineal hygiene (AOR 2.9; 1.0-8.4) and previous UTI (AOR 4.8; 1.5-15.2). Notably, 23.8 % of infections were asymptomatic. Conclusions: One third of pregnancies in this cohort were complicated by bacteriuria, driven largely by modifiable socio-behavioural factors and dominated by potentially resistant Gram-negative pathogens. Routine urine-culture screening at booking and late gestation, along with targeted interventions addressing anaemia, hygiene and poverty, should be prioritised to reduce maternal and neonatal morbidity. These findings echo regional studies and reinforce universal screening recommendations. Keywords: urinary-tract infection; pregnancy; prevalence; risk factors; Pakistan.